Handbook of entrepreneurship and sustainable development research - Kyro, Paula (Cheltenham Edward Elgar Publishing Ltd., 2015)
Today, research on entrepreneurship and sustainable development is influenced by a diverse array of approaches and perspectives. Drawing from this mélange, this book paints an illuminating picture of the historic and current understanding of the bond between entrepreneurship and sustainable development.
​Foreword / Holger Patzelt -- Acknowledgements Introduction: Expanding the Field of Research on Entrepreneurship and Sustainable Development / Paula Kyrö Part I: Historical roots and current conceptual  approaches for the alliance between entrepreneurship and sustainable development  1. To Grow or not to Grow? Entrepreneurship and Sustainable Development / Paula Kyrö -- 2. Sustainable Entrepreneurship: What It Is / Julia Katharina Binder and Frank-Martin Belz -- Part II: The Transformative approach to entrepreneushi for sustainable society 3. Socially Sustainable Entrepreneurship: A Case of Entrepreneurial Practice in Social Change and Stability /Toke Bjerregaard and Jakob Lauring 4. Entrepreneurship the Missing Link for Democratization and Development in Fragile Nations? / Steffen Farny and Santiago Delgado Calderon 5. Organizing Societal Entrepreneurship – A Cross Sector Challenge / Bengt Johannisson, Anders W. Johansson, Elisabeth Sundin, Karin Berglund, Erik Rosell, Birgitta Schwartz, Rebecca Stenberg and Malin Tillmar 6. Public Servants as Sustainability Policy Entrepreneurs in Australia - The Issues and Outcomes / Ganesh Keremane, Jennifer McKay and Zhifang Wu -- Part III Motivational and intentional approach to entrepreneurship and sustainable development  7. Recognizing First-person Opportunities for Sustainable Development / Benedetto Cannatelli, Laura Maria Ferri, Matteo Pedrini and Mario Molteni 8. Cooking up Solutions for Climate Change: The Role of Sustainable Entrepreneurs / Ivan Montiel and Tara Ceranic 9. An Exploratory Model of the Environmental Intention of SME Directors in Tunisia / Azzedine Tounés, Fafani Gribaa and Karim Messeghem 10. What Motivates Hotel Managers to Become Ecopreneurs: A Case Study on Spanish Tourism Sector / Samuel Gómez-Haro, Vera Ferrón-Vílchez, José Manuel de la Torre-Ruiz and Javier Delgado-Ceballos 11. The Impact of Micro Firm Every-day Practices on Sustainable Development in Local Communities / Rita Klapper and Paul Upham -- Part IV Industry and economy oriented approaches to entrepreneurship and sustainable development  12. The Renewable Energy Industry: Competitive Landscapes and Entrepreneurial Roles / Roberto Parente and Rosangela Feola 13. Commercializing Clean Technology Innovations – The Emergence of New Business in an Agency-Structure Perspective / Sofia Avdeitchikova and Lars Coenen 14. David versus Goliath: How Eco-entrepreneurs Transform Global Eco-systems / Kim Poldner and Oana Branzei 15. Market-Driven Capabilities and Sustainability of Alliances by Agricultural Small and Medium Enterprises / Mauro Sciarelli and Mario Tani 16. Entrepreneurial Functions by Organic Farmers / Marcus Dejardin, Jean Nizet and Denise Van Dam 17. The Entrepreneurial Contribution of Foreign-owned Companies to the Sustainable Development of Small Developing Host Economy / Tõnu Roolaht Index
Includes bibliographical refernces and index
Keywords: Production; ENTREPRENEURSHIP; SUSTAINABLE DEVELOPMENT; HANDBOOKS